Preparation method and application of coal-based carbon material constructed by dry ice-assisted cross-linking solidification

Through dry ice-assisted cross-linking curing, the preparation method of coal-based hard carbon materials is solved, and the problem of poor compatibility and dispersion of coal-based hard carbon materials during the carbonization process is achieved, and efficient sodium ion storage and electrochemical performance improvement is achieved.

CN119706800APending Publication Date: 2025-03-28INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411939601.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing coal-based hard carbon materials have poor compatibility and dispersion during the carbonization process, and the fine dispersion of soft carbon or hard carbon precursors in coal asphalt cannot be achieved, resulting in limited microcrystalline structure regulation and affecting electrochemical performance.

Method used

The preparation method of coal-based carbon materials for dry ice-assisted cross-linking is adopted to form high-active lattice defects and carbon radicals through steps such as crushing, screening, infiltration, deaze, density gradient sorting, dry ice hockey milling, low-temperature carbonization cross-linking and high-temperature carbonization, and high-temperature carbonization, high-efficiency loading and directional modification of carboxylic functional groups are achieved, and a large number of highly cross-linked connected interface structures are constructed.

Benefits of technology

The sodium storage performance and rate performance of coal-based hard carbon materials are improved, the disorder and layer spacing of carbonized products are enhanced, and the closed pore structure is formed, and stable and efficient sodium ion storage is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706800A_ABST
    Figure CN119706800A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electrochemical energy storage electrode materials, in particular to a preparation method and application of a coal-based carbon material constructed by dry ice-assisted cross-linking solidification. The method comprises the following steps: carrying out deliming and density gradient separation treatment on pulverized coal with a certain particle size to obtain ultra-pure coal sample macerals; by means of dry ice-assisted ball milling, efficient loading and directional modification of carboxyl functional groups are realized; the method comprises the following steps: performing low-temperature carbonization to obtain a homogenized oxidation-stabilized cross-linked coal maceral, and performing high-temperature carbonization to effectively avoid the problem that the oxidized coal has a skin-core structure due to melting in the subsequent carbonization process, thereby finally obtaining the coal-based carbon material with high pore connectivity. The method has the advantages of being stable in raw material source, low in cost, high in carbon yield, environmentally friendly, simple in treatment process and the like, the prepared coal-based carbon material shows excellent electrochemical performance as a supercapacitor electrode or a sodium ion / lithium ion battery negative electrode, and large-scale production is expected to be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage electrode materials, and in particular to a preparation method and application of a dry ice-assisted cross-linking and curing method for constructing a coal-based carbon material. Background Art

[0002] The aggravation of energy crisis and environmental pollution, coupled with the support of national policies, has enabled the energy storage industry to develop rapidly. Among them, sodium-ion batteries, due to their many advantages such as abundant resources, low cost, high energy conversion efficiency, long cycle life, maintenance-free, and good safety, perfectly meet the needs of the new energy field for low cost, long life and high safety performance, and have thus gained widespread attention from academia and industry. Given the above-mentioned unique technical advantages of sodium-ion batteries, they are expected to replace lead-acid batteries in the future and gradually achieve lead-free in fields such as low-speed electric vehicles. At the same time, facing the national strategic needs for large-scale energy storage and the rise of the home energy storage market under the coverage of smart grids, sodium-ion battery technology, as a new energy storage technology that is expected to replace lithium-ion batteries, will also play an important role. Therefore, it is imperative to develop sodium-ion batteries with low cost, abundant resources, and high safety. Insertion-type hard carbon is considered to be one of the most commercially promising candidate negative electrode materials due to its highly adjustable structure, small volume strain, low operating voltage, and high capacity.

[0003] At present, the raw materials for the production of hard carbon mainly include resin, biomass and mineral resources (such as coal). Among them, resin-based hard carbon has high specific capacity, but is expensive; biomass-based hard carbon has low carbonization yield and tap density, and the stability of raw material supply is poor. Coal has great development potential in low-cost sodium ion battery negative electrode materials due to its abundant resources, high carbon content, developed aromatic structure and low price. In the prior art, CN111293309A discloses a performance improvement method and application of coal-based sodium ion battery negative electrode materials, which improves the first coulomb efficiency and tap density by mixing coal-based materials with soft carbon precursors. Professor Xu Bin of Beijing University of Chemical Technology and others used natural polymer sucrose to modify lignite, coupled cross-linking co-carbonization to construct a heterogeneous structure hard carbon material, artificially increased the disorder and interlayer spacing of the carbon layer, and improved the electrochemical performance. However, the compatibility and dispersibility between soft carbon or hard carbon precursors and coal polycyclic aromatic hydrocarbon molecules are poor, and it is impossible to achieve fine dispersion of soft carbon or hard carbon precursors in coal tar pitch, and the microcrystalline structure of coal-based carbon materials can only be regulated within a limited range (ACSNano, 17 (2023) 24012-24021). Recently, in order to construct abundant closed pores in the coal-based hard carbon structure to significantly increase the platform capacity, a method of regulating the pore structure of the material by pre-treating the precursor with pore-forming agents or template agents has been derived. Professor Sun Fei of Harbin Institute of Technology and others used anthracite as raw material, and obtained a hard carbon sodium storage material with a high closed-pore content through KOH pre-activation and subsequent high-temperature carbonization, with a reversible capacity of 308.4 mAh g-1 [Advanced Functional Materials, 32 (2022) 2203725]. However, this process will pre-form a large number of open pores while introducing closed pores into hard carbon, which is not conducive to the improvement of the first effect. CN117401669A discloses a coal-based hard carbon material and its preparation method and application. The vitrinite in the coal is extracted by a physical fine sorting method, and its microstructure is adjusted by a suitable pre-oxidation method to enhance its sodium storage performance. However, in the traditional air oxidation process, the reaction speed of oxygen attacking free carbon is fast and is easily affected by diffusion, resulting in uneven oxidation degree of the sample and the presence of a skin-core structure. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a preparation method and application of dry ice-assisted cross-linking and curing to construct coal-based carbon materials. The preparation method aims to extract specific microscopic components in coal based on the microscopic characteristics of the microscopic components of coal and the differences in the surface properties of the particles; through dry ice-assisted ball milling, the microscopic component particles are broken and the C=C bonds in the condensed aromatic hydrocarbon molecules are broken under the induction of mechanical force, forming a large number of highly active lattice defects and carbon free radicals, and based on the CO2 two-electron activation mode, efficient loading and directional modification of carboxyl functional groups are achieved; and further low-temperature carbonization is performed to obtain a homogenized oxidatively stabilized cross-linked structure. Directed modification of carboxyl functional groups: On the one hand, as a hydrogen acceptor, it is converted into H2O and CO2, and the former is used to absorb heat and the latter to release heat to achieve in situ uniform activation of the carbon matrix. Combined with subsequent high-temperature carbonization, it is reorganized into closed pores, which helps the coal-based hard carbon negative electrode to store sodium stably and efficiently; on the other hand, a large number of C(O)-O cross-linked configurations are formed, and the large bond angles reduce the interaction between aromatic molecules during the carbonization process, constructing a highly cross-linked and largely connected interface structure, which serves as a channel for high-speed transmission of electrons and sodium ions, thereby improving the rate performance of coal-based hard carbon.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] The present invention provides a method for preparing a dry ice-assisted cross-linking and curing coal-based carbon material, comprising the following steps:

[0007] Step 1: crushing and screening the raw coal to obtain coal powder with a particle size less than 50 μm;

[0008] Step 2: The coal powder is placed in an ethanol solution to be fully soaked, and then deashed, filtered, washed with water until neutral, and dried to obtain an ultra-pure coal sample;

[0009] Step 3: subjecting the ultra-pure coal sample to density gradient separation and drying to obtain the ultra-pure coal sample microscopic components;

[0010] Step 4: placing the ultrapure coal sample microscopic components in a dry ice bath, and subjecting them to a carboxylation treatment by mechanical ball milling to obtain a carboxylated coal sample;

[0011] Step 5: subjecting the carboxylated coal sample to a low-temperature carbonization cross-linking reaction to obtain an oxidized cross-linked coal sample;

[0012] Step 6: subjecting the oxidized cross-linked coal sample to high-temperature carbonization treatment to obtain the coal-based carbon material.

[0013] Preferably, the raw coal in step 1 is at least one of lignite, bituminous coal and anthracite.

[0014] Preferably, the ratio of the coal sample to the ethanol solution in step 2 is 200 g:100-1000 mL.

[0015] Preferably, the vitrinite content in the microscopic components of the ultrapure coal sample in step 3 is 50-95%.

[0016] Preferably, in step 4, the mass ratio of the ultrapure coal sample microscopic components to dry ice is 5:6-200.

[0017] Preferably, the ball milling speed in step 4 is 100 to 800 rpm, and the time is 6 to 72 hours.

[0018] Preferably, the conditions for the low-temperature carbonization crosslinking reaction treatment in step 5 are: the atmosphere is one of air, nitrogen or argon, the temperature is 150-350°C, the heating rate is 1-5°C / min, and the insulation time is 30min-6h.

[0019] Preferably, the conditions for the high temperature carbonization treatment in step 6 are: temperature of 800-1500° C., heating rate of 1-10° C. / min, and holding time of 30 min-6 h.

[0020] The present invention also provides a coal-based carbon material prepared by the above-mentioned preparation method, wherein the specific surface area is 1-2000m 2 / g, interlayer spacing greater than 0.37nm, particle size D50 4-20μm, ash content ≤ 0.3wt%, tap density ≥ 0.45g / cm 3 .

[0021] The present invention also provides the use of the coal-based carbon material as a negative electrode material for sodium ion batteries, lithium ion batteries or supercapacitors.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention proposes a preparation method for coal-based carbon materials by dry ice-assisted ball milling, low-temperature cross-linking and curing, combined with high-temperature carbonization. Under the action of mechanochemistry, this strategy promotes the fragmentation of micro-component particles and the breaking of C=C bonds in condensed aromatic hydrocarbon molecules, forming a large number of highly active lattice defects, dangling bonds and carbon free radicals, inducing efficient loading and directional modification of carboxyl functional groups. The efficient loading of carboxyl functional groups in the precursor forms a large number of ester functional groups in the subsequent carbonization, which promotes the transformation of coal molecules from "thermoplastic" to "thermosetting", greatly limits the slip between carbon layers during high-temperature carbonization, effectively controls the development of porosity, enhances the disorder of the carbonization product, expands its interlayer spacing and the number of closed pores, and then improves its sodium storage performance.

[0024] 2. Directed modification of carboxyl functional groups can further serve as hydrogen acceptors and be converted into H2O and CO2. The former can be used to absorb heat and the latter to release heat, thereby achieving in-situ uniform activation of the carbon matrix. Combined with subsequent high-temperature carbonization, it can be reorganized into closed pores, which helps the coal-based hard carbon negative electrode to store sodium stably and efficiently.

[0025] 3. The preparation method of the present invention has simple equipment, easy-to-control operation process, stable product performance, and can realize large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the TEM image of the coal-based carbon material prepared in Example 1.

[0027] Figure 2 This is the TEM image of the coal-based carbon material prepared in Comparative Example 1.

[0028] Figure 3 The sodium ion battery charge and discharge curves of the coal-based carbon materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0029] The present invention is further described below with examples, but the protection scope of the present invention is not limited to the examples. Other changes and modifications made by those skilled in the art without departing from the spirit and protection scope of the present invention are still included in the protection scope of the present invention.

[0030] Example 1

[0031] (1) Put the bituminous coal into a pulverizer for pulverization, pass it through a 325-mesh sieve, and sieve to obtain coal powder with a particle size of less than 50 μm.

[0032] (2) Take 200 g of sieved coal powder, add it to 800 mL of ethanol solution to fully soak it, and then add 800 mL of deashing solution (the mass ratio of distilled water, 37% HCl, and 40% HF in the deashing solution is 50:30:20). After heating in a 95°C water bath for 4 hours, filter and remove impurities such as inorganic minerals in the coal sample, wash it with water until it is neutral, and dry it to obtain an ultra-pure coal sample.

[0033] (3) Take 40 g of ultrapure coal sample, add 500 mL of organic heavy liquid with a density of 1.30 kg / L (the volume ratio of organic heavy liquid is carbon tetrachloride:benzene=60:40), place it in a high-speed centrifuge, and centrifuge it at a speed of 8000 rps / min for 10 min. Pour the upper floating matter into a sand core funnel for suction filtration, and dry it to obtain the microscopic components of the ultrapure coal sample (the vitrinite content is about 95%), and its ash content is 0.1 wt%.

[0034] (4) Take 10 g of the ultrapure coal sample microscopic components obtained in step (3), add 300 g of dry ice, and ball mill for 12 h at a ball mill speed of 600 rpm to obtain a carboxylated coal sample.

[0035] (5) placing the carboxylated coal sample obtained in step (4) in a tubular furnace, heating the temperature to 350° C. at a heating rate of 1° C. / min under an argon atmosphere, keeping the temperature for 3 h, and cooling to room temperature to obtain an oxidative cross-linked coal sample.

[0036] (6) The oxidized cross-linked coal sample obtained in step (5) is placed in an inert atmosphere, heated to 1400° C. at a heating rate of 2° C. / min under an argon environment, kept at that temperature for 2 h, and cooled to room temperature to obtain a coal-based carbon material.

[0037] The specific surface area of ​​the coal-based carbon material prepared in Example 1 is 2.8 m 2 / g, interlayer spacing greater than 0.388nm, particle size D50 of 5.6um, ash content of 0.1wt%, tap density of 0.87g / cm 3 . The prepared coal-based carbon material was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil. After drying, the electrode was cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode has a reversible specific capacity of 340.8mAh / g at a current density of 20mA / g, and a first coulombic efficiency of 89%.

[0038] The above-cut electrode was further used as the working electrode, the lithium sheet as the reference electrode and the counter electrode, and 1MLiPF6 (ethylene carbonate and dimethyl carbonate volume ratio of 3:7) solution was used as the electrolyte, and assembled in an Ar atmosphere glove box to form a CR2032 button cell. After testing, the hard carbon negative electrode had a current density of 50mA / g, a reversible specific capacity of 510mAh / g, and a first coulombic efficiency of 78%.

[0039] Example 2

[0040] (1) Put the bituminous coal into a pulverizer for pulverization, pass it through a 325-mesh sieve, and sieve to obtain coal powder with a particle size of less than 50 μm.

[0041] (2) Take 200 g of sieved coal powder, add it to 100 mL of ethanol solution to fully soak it, and then add 800 mL of deashing solution (the mass ratio of distilled water, 37% HCl, and 40% HF in the deashing solution is 50:30:20). After heating in a 95°C water bath for 4 hours, filter and remove impurities such as inorganic minerals in the coal sample, wash it with water until it is neutral, and dry it to obtain an ultra-pure coal sample.

[0042] (3) Take 40 g of ultrapure coal sample, add 500 mL of organic heavy liquid with a density of 1.30 kg / L (the volume ratio of organic heavy liquid is carbon tetrachloride:benzene=60:40), place it in a high-speed centrifuge, and centrifuge it at a speed of 8000 rps / min for 10 min. Pour the upper floating matter into a sand core funnel for suction filtration, and dry it to obtain the microscopic components of the ultrapure coal sample (the vitrinite content is about 90%), and its ash content is 0.18 wt%.

[0043] (4) Take 10 g of the ultrapure coal sample microscopic components obtained in step (3), add 12 g of dry ice, and ball mill for 72 h at a ball mill speed of 100 rpm to obtain a carboxylated coal sample.

[0044] (5) placing the carboxylated coal sample obtained in step (4) in a tubular furnace, heating the temperature to 150° C. at a heating rate of 1° C. / min under an argon atmosphere, keeping the temperature for 2 h, and cooling to room temperature to obtain an oxidative cross-linked coal sample.

[0045] (6) The oxidized cross-linked coal sample obtained in step (5) is placed in an inert atmosphere, heated to 1100° C. at a heating rate of 2° C. / min under an argon environment, kept at that temperature for 2 h, and cooled to room temperature to obtain a coal-based carbon material.

[0046] The specific surface area of ​​the coal-based carbon material prepared in Example 2 is 10 m 2 / g, interlayer spacing greater than 0.38nm, particle size D50 of 8μm, ash content of 0.3wt%, tap density of 0.85g / cm 3. The prepared coal-based carbon material was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil. After drying, the electrode was cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode has a reversible specific capacity of 330.8mAh / g at a current density of 20mA / g, and a first coulombic efficiency of 86%.

[0047] The above-cut electrode was further used as the working electrode, the lithium sheet as the reference electrode and the counter electrode, and 1MLiPF6 (ethylene carbonate and dimethyl carbonate volume ratio of 3:7) solution was used as the electrolyte, and assembled in an Ar atmosphere glove box to form a CR2032 button cell. After testing, the hard carbon negative electrode had a reversible specific capacity of 485mAh / g at a current density of 50mA / g and a first coulombic efficiency of 73%.

[0048] Example 3

[0049] (1) Place the anthracite into a pulverizer for pulverization, pass through a 325-mesh sieve, and sieve to obtain coal powder with a particle size of less than 50 μm.

[0050] (2) Take 200 g of sieved coal powder, add it to 1000 mL of ethanol solution to fully soak it, and then add 800 mL of deashing solution (the mass ratio of distilled water, 37% HCl, and 40% HF in the deashing solution is 50:30:20). After heating in a 95°C water bath for 4 hours, filter and remove impurities such as inorganic minerals in the coal sample, wash it with water until it is neutral, and dry it to obtain an ultra-pure coal sample.

[0051] (3) Take 40 g of ultrapure coal sample, add 500 mL of organic heavy liquid with a density of 1.30 kg / L (the volume ratio of organic heavy liquid is carbon tetrachloride:benzene=60:40), place it in a high-speed centrifuge, and centrifuge it at a speed of 8000 rps / min for 10 min. Pour the upper floating matter into a sand core funnel for suction filtration, and dry it to obtain the microscopic components of the ultrapure coal sample (the vitrinite content is about 85%), and its ash content is 0.2 wt%.

[0052] (4) Take 10 g of the ultrapure coal sample microscopic components obtained in step (3), add 400 g of dry ice, and ball mill for 6 h at a ball mill speed of 800 rpm to obtain a carboxylated coal sample.

[0053] (5) placing the carboxylated coal sample obtained in step (4) in a tubular furnace, heating the temperature to 300° C. at a heating rate of 1° C. / min in an air atmosphere, keeping the temperature for 6 h, and cooling the temperature to room temperature to obtain an oxidatively cross-linked coal sample.

[0054] (6) The oxidized cross-linked coal sample obtained in step (5) is placed in an inert atmosphere, heated to 1500° C. at a heating rate of 5° C. / min under an argon environment, kept at that temperature for 6 h, and cooled to room temperature to obtain a coal-based carbon material.

[0055] The specific surface area of ​​the coal-based carbon material prepared in Example 3 is 4 m 2 / g, interlayer spacing greater than 0.376nm, particle size D50 of 8μm, ash content of 0.3wt%, tap density of 0.90g / cm 3 . The prepared coal-based carbon material was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil. After drying, the electrode was cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode has a reversible specific capacity of 310.8mAh / g at a current density of 20mA / g, and a first coulombic efficiency of 89%.

[0056] Example 4

[0057] (1) The lignite is placed in a pulverizer for pulverization, passed through a 325-mesh sieve, and sieved to obtain coal powder with a particle size of less than 50 μm.

[0058] (2) Take 200 g of sieved coal powder, add it to 800 mL of ethanol solution to fully soak it, and then add 800 mL of deashing solution (the mass ratio of distilled water, 37% HCl, and 40% HF in the deashing solution is 50:30:20). After heating in a 95°C water bath for 4 hours, filter and remove impurities such as inorganic minerals in the coal sample, wash it with water until it is neutral, and dry it to obtain an ultra-pure coal sample.

[0059] (3) Take 40 g of ultrapure coal sample, add 500 mL of organic heavy liquid with a density of 1.30 kg / L (the volume ratio of organic heavy liquid is carbon tetrachloride:benzene=60:40), place it in a high-speed centrifuge, and centrifuge it at a speed of 8000 rps / min for 10 min. Pour the upper floating matter into a sand core funnel for suction filtration, and dry it to obtain the microscopic components of the ultrapure coal sample (the vitrinite content is about 90%), and its ash content is 0.1 wt%.

[0060] (4) Take 10 g of the ultrapure coal sample microscopic components obtained in step (3), add 200 g of dry ice, and ball mill for 10 h at a ball mill speed of 600 rpm to obtain a carboxylated coal sample.

[0061] (5) placing the carboxylated coal sample obtained in step (4) in a tubular furnace, heating the temperature to 350° C. at a heating rate of 1° C. / min in an air atmosphere, keeping the temperature for 4 h, and cooling to room temperature to obtain an oxidatively cross-linked coal sample.

[0062] (6) The oxidized cross-linked coal sample obtained in step (5) is placed in an inert atmosphere, heated to 800° C. at a heating rate of 1° C. / min under an argon environment, kept at that temperature for 3 h, and cooled to room temperature to obtain a coal-based carbon material.

[0063] The specific surface area of ​​the coal-based carbon material prepared in Example 4 is 1500 m 2 / g, interlayer spacing greater than 0.38nm, particle size D50 of 8μm, ash content of 0.1wt%, tap density of 0.45g / cm 3 The coal-based carbon material, acetylene black and polytetrafluoroethylene were added in a mass ratio of 85:10:5, mixed and rolled into a film and then punched into a diameter of 1 cm. 2 The electrode sheet uses 6M KOH as the electrolyte. When the current density is 1A / g, its specific capacitance is 150F / g.

[0064] Example 5

[0065] (1) Put the bituminous coal into a pulverizer for pulverization, pass it through a 325-mesh sieve, and sieve to obtain coal powder with a particle size of less than 50 μm.

[0066] (2) Take 200 g of sieved coal powder, add it to 300 mL of ethanol solution to fully soak it, and then add 800 mL of deashing solution (the mass ratio of distilled water, 37% HCl, and 40% HF in the deashing solution is 50:30:20). After heating in a 95°C water bath for 4 hours, filter and remove impurities such as inorganic minerals in the coal sample, wash it with water until it is neutral, and dry it to obtain an ultra-pure coal sample.

[0067] (3) Take 40 g of ultrapure coal sample, add 500 mL of organic heavy liquid with a density of 1.30 kg / L (the volume ratio of organic heavy liquid is carbon tetrachloride:benzene=60:40), place it in a high-speed centrifuge, and centrifuge it at a speed of 8000 rps / min for 10 min. Pour the upper floating matter into a sand core funnel for suction filtration, and dry it to obtain the microscopic components of the ultrapure coal sample (the vitrinite content is about 80%), whose ash content is 0.2 wt%.

[0068] (4) Take 10 g of the ultrapure coal sample microscopic components obtained in step (3), add 200 g of dry ice, and ball mill for 24 h at a ball mill speed of 500 rpm to obtain a carboxylated coal sample.

[0069] (5) The carboxylated coal sample obtained in step (4) is placed in a tubular furnace, heated to 300° C. at a heating rate of 1° C. / min under an argon atmosphere, kept at that temperature for 6 h, and cooled to room temperature to obtain an oxidative cross-linked coal sample.

[0070] (6) The oxidized cross-linked coal sample obtained in step (5) is placed in an inert atmosphere, heated to 1300° C. at a heating rate of 2° C. / min under an argon environment, kept at that temperature for 2 h, and cooled to room temperature to obtain a coal-based carbon material.

[0071] The specific surface area of ​​the coal-based carbon material prepared in Example 5 is 4.1 m 2 / g, interlayer spacing greater than 0.382nm, particle size D50 of 5.6μm, ash content of 0.3wt%, tap density of 0.85g / cm 3 . The prepared coal-based carbon material was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil. After drying, the electrode was cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode has a reversible specific capacity of 310.8mAh / g at a current density of 20mA / g, and a first coulombic efficiency of 88%.

[0072] Comparative Example 1

[0073] The difference between this comparative example and Example 1 is that the comparative example does not undergo the dry ice-assisted ball milling process described in step (4). The other steps and parameters of Comparative Example 1 are the same as those of Example 1.

[0074] The coal-based carbon material prepared in Comparative Example 1 was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil, and after drying, the pole pieces were cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate was 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode had a reversible specific capacity of 269.8mAh / g at a current density of 20mA / g, and a first coulombic efficiency of 82.8%.

[0075] Comparative Example 2

[0076] The difference between this comparative example and Example 1 is that the oxidation crosslinking treatment method in steps (4) and (5) is an air pre-oxidation method, specifically, the ultrapure coal sample obtained in step (3) is placed in a tubular furnace, heated to 350°C at a heating rate of 1°C / min in an air atmosphere, kept warm for 3 hours, and cooled to room temperature. The other steps and parameters of Comparative Example 1 are the same as those of Example 1.

[0077] The coal-based carbon material prepared in Comparative Example 1 is mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry is evenly scraped onto the current collector aluminum foil. After drying, the pole piece is cut. The battery is assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode has a current density of 30mA / g, a reversible specific capacity of 110.8mAh / g, and a first coulombic efficiency of 80%. After testing, the hard carbon negative electrode has a current density of 20mA / g, a reversible specific capacity of 280.8mAh / g, and a first coulombic efficiency of 85%.

[0078] Figure 1 and Figure 2 TEM images of coal-based carbon materials prepared in Example 1 and Comparative Example 1. It can be seen from the figure that the coal-based carbon material prepared in Comparative Example 1 presents a locally long-range ordered graphite-like structure; while the coal-based carbon material prepared in Example 1 is composed of a randomly oriented small-sized carbon layer structure, which has the characteristics of long-range disorder and short-range order. This shows that the efficient loading and directional modification of carboxyl functional groups promote the formation of ester functional groups and effectively inhibit the rearrangement of early carbon layers. Subsequently, during the carbonization process, the removal of oxygen expands the interlayer spacing, which is conducive to the development of ultramicropores and the formation of disordered structures.

[0079] Figure 3 The charge and discharge curves of the sodium ion battery of the coal-based carbon material prepared in Example 1 and Comparative Example 1 are shown. The discharge characteristics of the slope area and the platform area of ​​Example 1 are improved compared with those of Comparative Example 1, the first charge capacity is increased from 269.8 mAh / g to 340.8 mAh / g, and the first coulomb efficiency is increased to 89%.

Claims

1. A method for preparing a dry ice-assisted cross-linking and curing coal-based carbon material, characterized in that: The following steps are involved: Step 1: crushing and screening the raw coal to obtain coal powder with a particle size less than 50 μm; Step 2: The coal powder is placed in an ethanol solution to be fully soaked, and then deashed, filtered, washed with water until neutral, and dried to obtain an ultra-pure coal sample; Step 3: subjecting the ultra-pure coal sample to density gradient separation and drying to obtain the ultra-pure coal sample microscopic components; Step 4: placing the ultrapure coal sample microscopic components in a dry ice bath, and subjecting them to a carboxylation treatment by mechanical ball milling to obtain a carboxylated coal sample; Step 5: subjecting the carboxylated coal sample to a low-temperature carbonization cross-linking reaction to obtain an oxidized cross-linked coal sample; Step 6: subjecting the oxidized cross-linked coal sample to high-temperature carbonization treatment to obtain the coal-based carbon material.

2. The method for preparing a dry ice-assisted cross-linking and curing coal-based carbon material according to claim 1, characterized in that: The raw coal in step 1 is at least one of lignite, bituminous coal and anthracite.

3. The method for preparing a dry ice-assisted cross-linking and curing coal-based carbon material according to claim 1, characterized in that: In step 2, the ratio of the coal sample to the ethanol solution is 200 g: 100-1000 mL.

4. The method for preparing a dry ice-assisted cross-linking and curing coal-based carbon material according to claim 1, characterized in that: In the step 3, the vitrinite content in the microscopic components of the ultrapure coal sample is 50-95%.

5. The method for preparing a dry ice-assisted cross-linking and curing coal-based carbon material according to claim 1, characterized in that: In step 4, the mass ratio of the ultrapure coal sample microscopic components to the dry ice is 5:6-200.

6. The method for preparing a dry ice-assisted cross-linking and curing coal-based carbon material according to claim 1, characterized in that: In step 4, the ball milling speed is 100 to 800 rpm, and the time is 6 to 72 hours.

7. The method for preparing a dry ice-assisted cross-linking and curing coal-based carbon material according to claim 1, characterized in that: The conditions for the low-temperature carbonization crosslinking reaction treatment in step 5 are: the atmosphere is one of air, nitrogen or argon, the temperature is 150-350° C., the heating rate is 1-5° C. / min, and the insulation time is 30 min-6 h.

8. The method for preparing a dry ice-assisted cross-linking and curing coal-based carbon material according to claim 1, characterized in that: The conditions for high temperature carbonization treatment in step 6 are: temperature of 800-1500° C., heating rate of 1-10° C. / min, and heat preservation time of 30 min-6 h.

9. The coal-based carbon material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The specific surface area of ​​the coal-based carbon material is 1-2000m 2 / g, interlayer spacing greater than 0.37nm, particle size D50 4-20μm, ash content ≤ 0.3wt%, tap density ≥ 0.45g / cm 3 .

10. The use of the coal-based carbon material according to claim 9, characterized in that: As negative electrode material for sodium-ion batteries, lithium-ion batteries or supercapacitors.

Citation Information

Patent Citations

  • Coal-based hard carbon material as well as preparation method and application thereof

    CN117401669A